GE_GERICHTE P/19803/2014 vom 16. September 2015 - GE Cour de justice (2015)
DÉCISION DE RENVOI ; MESURE THÉRAPEUTIQUE INSTITUTIONNELLE ; INTERNEMENT(DROIT PÉNAL) ; EXPERTISE ; MALADIE MENTALE ; MEURTRE ; TENTATIVE(DROIT PÉNAL) | CP.111; CP.56; CP.64.al1